The influence of workplace relationships and job satisfaction of private universities in Mogadishu: employee performance as a mediator variable - Mohamed, Mohamud Ahmed; Mohamud, Fartun Ahmed Sheikh; Mohamud, Ibrahim Hassan; Farah, Mohamed Ali (Frontiers in Education, 2024)
Drawing on literature and empirical studies, this research examined the relationships between employers and employees, and among employees, and their impact on employee performance and job satisfaction at private universities in Mogadishu. Using a quantitative methodology, 198 academic staff members were selected for representativeness. Data on employee performance, job satisfaction, and workplace relationships were gathered via questionnaires and analyzed using Smart PLS 4 and SPSS version 23. The findings indicated that positive employer-employee relationships significantly enhance job satisfaction and employee performance. Conversely, while connections among academic staff were linked to higher job satisfaction, they negatively impacted performance outcomes, suggesting complex workplace dynamics. The research revealed significant effect sizes, highlighting the practical impact of these relationships, showing that strong employer-employee relationships could notably improve engagement, reduce attrition, and enhance performance in private universities. These relationships accounted for 31.7% of the variability in performance outcomes, underscoring their real-world relevance. The study provides actionable insights for educational institutions to improve job satisfaction and performance by fostering positive employer-employee relationships through structured support programs, regular feedback, and team-building activities. Suggestions for further research were offered to address the identified shortcomings.